2021
DOI: 10.1371/journal.pntd.0009117
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ivermectin on onchocerciasis in villages co-endemic for lymphatic filariasis in an area of onchocerciasis recrudescence in Burkina Faso

Abstract: In Burkina Faso, onchocerciasis was no longer a public health problem when the WHO Onchocerciasis Control Programme in West Africa closed at the end in 2002. However, epidemiological surveillance carried out from November 2010 to February of 2011, showed a recrudescence of infection in the Cascades Region. This finding was made at a time when ivermectin, a drug recommended for the treatment of both onchocerciasis and lymphatic filariasis, had been distributed in this area since 2004 for the elimination of lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It seems that the situation had been stabilized after 1995 by the MDA, but there had been no obvious improvement and onchocerciasis was still a public health problem, and this was probably the result of poor geographic coverage [ 24 ]. In a multi-country study, it had been shown that CDTI produced better coverage than other methods of MDA (such as mobile teams and Community Based Treatment with Ivermectin) [ 40 ], and so the change of strategy from control to elimination was also accompanied by a change to biannual CDTI in 2013 after its successful introduction to control the recrudescence in Cascades region in 2011 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the situation had been stabilized after 1995 by the MDA, but there had been no obvious improvement and onchocerciasis was still a public health problem, and this was probably the result of poor geographic coverage [ 24 ]. In a multi-country study, it had been shown that CDTI produced better coverage than other methods of MDA (such as mobile teams and Community Based Treatment with Ivermectin) [ 40 ], and so the change of strategy from control to elimination was also accompanied by a change to biannual CDTI in 2013 after its successful introduction to control the recrudescence in Cascades region in 2011 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the 2018 survey are very encouraging because they suggest that the region is progressing toward onchocerciasis elimination. A previous study assessing the effectiveness of the CDTI in the Cascades region, (where onchocerciasis had also been recrudescent), showed that the strategy could be applied effectively for control of onchocerciasis in Burkina Faso [ 41 ], and other studies in other parts of West Africa, East Africa and Ethiopia have also demonstrated successful interruption of onchocerciasis transmission by biannual CDTI [ 16 , 17 , 42 , 43 , 44 , 45 ]. Therefore, it seems probable that continuation of CDTI in the Sud-Ouest region of Burkina Faso, with rigorous supervision of the community distributors by health professionals, could quickly reach the goal of interruption of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Our regression model also indicated a double-fold increase in risk of infection among those who did not take ivermectin compared with those who did. Studies have reported the efficacy of ivermectin in reducing mf load and subsequently reduce transmission [ 39 , 40 ]. Therefore, there is a need to investigate the reasons for this shortfall and how to subsequently improve geographical coverage if we are to meet the elimination target.…”
Section: Discussionmentioning
confidence: 99%